Joseph Ball correspondence - Ball, Joseph, 1689-
Letterbook containing letters (1743-1759) of Ball, an uncle of George Washington, and letters (1760-1780) of Rawleigh Downman, Ball's son-in-law. Includes notes concerning their family.
Microfilm edition of the Rawleigh Downman correspondence available
Microfilm produced from originals in the Manuscript Division.
Negative photostats.
Lawyer and landowner.
Collection material in English.
Keywords: Downman, Rawleigh -- Correspondence; Washington, George, -- 1732-1799.; Ball family; Lawyers; Landowners